Youth Smoking in Indonesia: Demographic Determinants and Policy Imperatives in a Middle Income Country - Ramlan, Pratiwi; Syam, Sadli; Arwan; Firmansyah; Anas, Adhe Sofyan; Alchamdani (Medicor : Journal of Health Informatics and Health Policy, 2024)
Tobacco use among Indonesian youth remains alarmingly high despite ongoing anti-smoking initiatives, posing a significant public health challenge. This study aimed to identify the prevalence and key demographic determinants of youth smoking in Indonesia, utilizing a cross-sectional analysis of the 2023 Riskesdas national health survey and a 2024 Ministry of Health press release. Variables examined included age, gender, education, income level, and urban or rural residency, analyzed using frequency distributions, cross-tabulations, and logistic regression. Results revealed that smoking rates peaked among youth aged 20–24 (18.5%), with males and individuals from lower education and income backgrounds at greater risk. Urban youth and those who began smoking before age 15 were also more likely to develop long-term dependence. Socioeconomic disadvantage, limited health literacy, and weak enforcement of tobacco laws emerged as major risk factors. The findings highlight the need for comprehensive, multi-sectoral, and culturally adapted strategies including strengthened school-based programs, community engagement, stricter tobacco advertising bans, and increased tobacco taxation to effectively reduce youth smoking. Coordinated actions across education, policy, healthcare, and media sectors are critical for protecting Indonesia’s next generation from the harms of tobacco.